Strigolactones as a hormonal hub for the acclimation and priming to environmental stress in plants. (21st October 2022) - Trasoletti, Marta; Visentin, Ivan; Campo, Eva; Schubert, Andrea; Cardinale, Francesca
Abstract: Strigolactones are phytohormones with many attributed roles in development, and more recently in responses to environmental stress. We will review evidence of the latter in the frame of the classic distinction among the three main stress acclimation strategies (i.e., avoidance, tolerance and escape), by taking osmotic stress in its several facets as a non‐exclusive case study. The picture we will sketch is that of a hormonal family playing important roles in each of the mechanisms tested so far, and influencing as well the build‐up of environmental memory through priming. Thus, strigolactones appear to be backstage operators rather than frontstage players, setting the tune of acclimation responses by fitting them to the plant individual history of stress experience. Summary statement: Strigolactones act as backstage operators rather than frontstage players in stress acclimation strategies (avoidance, tolerance, possibly, escape), by tuning them to the plant individual history of stress experience.